Smart Wind Farm Management Based On Wsn (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Super Grid Lead Node Path, Partitioned Grid Lead Node Path and Shortest Super Grid Lead Node Path are the three network operations proposed for efficient routing. The grid lead node is selected by calculating their value of node degree and the node degree value is relied upon the metrics such as distance, energy and the communication range. Operation of the network in all three proposed protocols SGLN, PCLNP and SSGLN undergoes some particular number of communication rounds. The grid lead node is selected by calculating the energy values. The proposed mechanism includes GL selection, SGL selection done using fuzzy logic with the metrics such as implicit distance and implicit energy. MST is applied for route establishment and finally data transmission is processed. GL election is done based upon distributed manner and SGL selection is done using centralized process. Simulation results proved the efficiency of the proposed protocols compared to their conventional TLCRA scheme.